Collaborative Governance in the Implementation of Special Autonomy in Papua - Stepi Anriani (Budapest International Research and Critics University, 2022)
The Special Autonomy Policy in Papua is an effort by the Indonesian government in dealing with a number of problems that exist in Papua related to poverty, lagging development, response to conflict situations and overcoming the separatist movement. In the implementation of the Special Autonomy policy, a collaborative approach is needed so that all stakeholders can be well involved, namely state and non-state actors. The purpose of this study is to analyze Collaborative Governance in implementing the Special Autonomy Policy in Papua. The method used in this research is qualitative with interviews, focus group discussions, observation and literature study. The research locations were carried out in Jakarta and Jayapura Papua in 2018-2021. The purpose of this study is to analyze Collaborative Governance in the Special Autonomy policy in Papua. In this study, using the theory and concept of collaboration on the theory of Wanna (2008) which consists of the planning stage, program implementation stage, resource management stage and the monitoring and evaluation stage of Special Autonomy. The results show that in Collaborative Governance, the Special Autonomy Policy in Papua is in the planning stage at the medium-low level of collaboration, the implementation stage is at the lowest collaboration level, the resource management stage is in the low collaboration stage, while the supervision stage is in the low collaboration level.